1998
DOI: 10.1086/513825
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Measles Viruses Isolated in the United States, 1995–1996

Abstract: Genetic analysis was conducted on 28 wild type measles viruses isolated from outbreaks or cases in the United States during 1995-1996. These viruses were members of at least 6 distinct genetic groups. However, none of these viruses was related to the group 2 viruses that were associated with the resurgence of measles in the United States between 1989 and 1992 except for a single importation from the Philippines. The sequence data support and extend previous findings showing that transmission of group 2 viruses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 10 publications
0
68
0
Order By: Relevance
“…A similar argument can be applied to MV. The mutation rate for MV measured here is still high enough to provide a paradox with the low replacement rate for the H gene of MV from isolates in the field (24,25). The number of replications involved in the transmissions of virus between at least 26 infected patients in an outbreak sustained over 1 year must be in the order of trillions, and multiplying this with the lowest rate determined here of 0.03 per genome replication still indicates the tremendous selection pressure that is required to explain the low replacement rate for MV in the field.…”
Section: Discussionmentioning
confidence: 78%
“…A similar argument can be applied to MV. The mutation rate for MV measured here is still high enough to provide a paradox with the low replacement rate for the H gene of MV from isolates in the field (24,25). The number of replications involved in the transmissions of virus between at least 26 infected patients in an outbreak sustained over 1 year must be in the order of trillions, and multiplying this with the lowest rate determined here of 0.03 per genome replication still indicates the tremendous selection pressure that is required to explain the low replacement rate for MV in the field.…”
Section: Discussionmentioning
confidence: 78%
“…Analysis of viruses isolated from measles cases and outbreaks in the United Stated between 1994 and 2001 failed to detect ongoing transmission of an endemic genotype ( figure 1). Rather, the diversity of genotypes detected in the last 7 years is indicative of multiple, imported sources of virus [28,29]. Likewise, the diversity of genotypes detected in Australia, Canada, and the United Kingdom is similar to that observed in the United States, suggesting frequent importation of measles and lack of endemic circulation of virus [30][31][32][33].…”
Section: Global Distribution Of Measles Genotypesmentioning
confidence: 90%
“…Endemic transmission has been eliminated in many areas of the world, including most of the countries in the Western Hemisphere. Both virologic and epidemiologic data collected in the United States between 1989 and 2000 indicated that interruption of transmission of the genotype D3 viruses that were associated with the measles resurgence of the early 1990s was achieved in 1993 and subsequently maintained [14,28]. Analysis of viruses isolated from measles cases and outbreaks in the United Stated between 1994 and 2001 failed to detect ongoing transmission of an endemic genotype ( figure 1).…”
Section: Global Distribution Of Measles Genotypesmentioning
confidence: 99%
See 2 more Smart Citations